Historical background of the academic dance - Colomer Sánchez, Ana; Lévéder-Le Pottier Bernard, Gaël (Research in Dance Education, 2026)
This article takes the reader on a tour of the origins of academic dance that begins with the arrival of Catherine de’ Medici to the French court as the future consort of King Henry II. The emerging Humanism ideas of the Renaissance renew the concept of «dance» that evolves from Medieval sin, when mundane was denied, to a performing art whose scenic space will dominate the French shortly after the life of its age, for show and power to get identified, especially from the coronation of Louis XIV and the environment of the Palace of Versailles. In this tour through history, we shall stress as far as possible the fact that improvements in scenography and theatrical machinery, the regulation of popular dances or the situation of the public in relation to the stage, among others, will deeply influence on the renewal of the dance techniques and will become the genesis of the rules that regulate the methodology of Classical Dance the way we know it nowadays, to end up in the first European School of Academic Dance and the notation of its practice.
Keywords: baile; escuela de baile; historia de la danza; Renacimiento; técnica de baile